THE ROLE OF SELF EFFICACY IN IMPROVING EMPLOYEE PERFORMANCE SUPPORTED BY ORGANIZATIONAL CULTURE AND CAREER DEVELOPMENT - Khaery, Muhammad Rafi; Maberur, Iqbal; Solahudin, Ade (Ridwan Institute, 2024)
This study aims to find out the influence of organizational culture, career development development, and self-efficacy on employee performance. The population in this study is all employees of the Tirta Darma Ayu Indramayu Regional Drinking Water Company (PDAM) which totals 146 people, with a sample of 110 people. The method used in this study uses one of the saturated sampling techniques. To analyze the data, the use of Structural Equation Modeling (SEM) in model creation as well as hypothesis testing in PLS 3.0 statistical software. The two main parameters built are to test the validity of the construct (convergent and discriminatory validity) and the internal consistency of the construct (reliability). After that, perform bootstrapping tests to get the test results for each hypothesis. The results of this study show that the Self-efficacy Variable (X1) partially has a positive or significant effect on the performance of employees (Y) at the Indramayu Regional Drinking Water Company. The Organizational Culture Variable (X2) partially has a positive or significant effect on the performance of employees (Y) at the Indramayu Regional Drinking Water Company The Career Development Variable (X3) partially has a positive or significant effect on the performance of employees (Y) at the Indramayu Regional Drinking Water Company.